Environmentally assisted fatique crack development in aluminium-based metal matrix composites. - Julia Diane Shields (2003)
"Aluminium alloys have been used successfully in a variety of commercial systems due to their unusual combination of properties. These include low density, good corrosion resistance and excellent mechanical properties. However, they also have disadvantages which include a low resistance to fracture and fatigue under load. The addition of reinforcing particles improves these properties, but it may also upset the delicate balance which has been achieved over many years of fine tuning. This study addresses the areas of uncertainty concerning environmental sensitivity in a leading aluminium based silicon carbide particle reinforced metal matrix composite, under conditions of direct interest to the aerospace industry. The materials studied are 2XXX series aluminium alloys, AMC225, mechanically alloyed and powder blended conditions. The environments to which they have been subjected include immersion in 3.5% sodium chloride solution, from zero to 72 hours and a fog atmosphere of the same composition. It has been found that soaking the materials in this salt solution has a significant detrimental effect on fatigue performance, even after relatively short soaks of 8 hours. The LCF performance is independent of processing route in the T4 condition alloys. Lives to failure are dramatically reduced on the introduction of a saline environment, in which the process of corrosion pitting is implicated. Sensitivity to a salt fog environment is independent of waveform frequency. A "long crack" trend has been defined for DeltaK>8MNm-3/2, which corresponds to the Paris regime, with Paris exponents of m=3.57 and c=3.49 x 10-11."